Investigating the Operational Feasibility of Waste Management at Integrated Waste Management Sites in Balikpapan City - Putri, Dian Ameliana; Pratomo, Rahmat Aris (Universitas Lambung Mangkurat, 2024)
Referring to the Balikpapan City Medium-Term Development Plan for 2021-2026, the percentage of waste transported to the Final Waste Processing Site (FWPS) is 75.45%, which is higher than the percentage of waste management. As of now, there are 2 Integrated Waste Management Sites (IWMS) in Balikpapan, namely MRF and ITF. Based on data from 2019, waste management at MRF decreased by 51.14%. Meanwhile, ITF only utilizes 25.98% - 31.31% of total incoming waste, with the remainder being sent to Manggar FWPS. This decline in performance is also related to the deteriorating condition of approximately 62% of waste management infrastructure in Balikpapan, so evaluation of the operational aspects of waste management becomes a crucial factor in addressing this issue. In addition, the ideal condition of waste management according to standards serves as the main indicator in assessing the performance of waste management. This research aims to evaluate operational aspects of waste management at Balikpapan IWMS by applicable regulations. Analysis methods used are mass balance analysis and operational performance analysis. Research findings show that waste management at IWMS Balikpapan City can reduce the volume of waste in Balikpapan City. However, the operational performance of MRF did not meet established standards, especially in terms of waste removal and processing systems, with a score of 19. On the other hand, ITF is considered sufficient by provisions of PUPR Minister Regulation Number 03 of 2013 and Indonesian National Standard 19-2454-2002 with a score of 23.